Effect of Magnetic Field on the Properties of Flowing Lubricating Cooling Liquids used in Manufacturing Process - Erkin Odilov; Ma’murjonov Dilshod; Umidjon Mardonov (Research Parks Publishing LLC, 2021)
In this paper, the effect of magnetic field on cooling liquids, which are used in the heat treatment process in manufacturing, was studied. We chose three different lubricating cooling liquids that are commonly used in local manufacturing factories to conduct the experiment. Three main properties of these lubricoolants such as boiling point and kinematic viscosity were analyzed after magnetizing them. The article shows the results of these comparisons and analyze the magnetic field influence on different types of fluids